1998
DOI: 10.1007/s004390050781
|View full text |Cite
|
Sign up to set email alerts
|

Elite endurance athletes and the ACE I allele - the role of genes in athletic performance

Abstract: Genetic markers that might contribute to the making of an elite athlete have not been identified. Potential candidate genes might be found in the renin-angiotensin pathway, which plays a key role in the regulation of both cardiac and vascular physiology. In this study, DNA polymorphisms derived from the angiotensin converting enzyme (ACE), the angiotensin type 1 receptor (AT1) and the angiotensin type 2 receptor (AT2) were studied in 64 Australian national rowers. Compared with a normal population, the rowers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
209
2
17

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(236 citation statements)
references
References 8 publications
8
209
2
17
Order By: Relevance
“…Not many candidate genes associated with physical functioning have been identified. One suggestion has been a polymorphism in the gene encoding the Angiotensin Converting Enzyme, but the association was found only in small samples of young healthy males and elite athletes [Montgomery et al, 1998;Williams et al, 2000;Gayagay et al, 1998;Myerson et al, 1999], and not in all studies [Taylor et al, 1999;Rankinen et al, 2000a,b] and not among the elderly [Frederiksen et al, 2002]. A polymorphism in the gene encoding a receptor for vitamin D has been associated with grip strength in postmenopausal women, but only in a nonobese subgroup [Geusens et al, 1997].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not many candidate genes associated with physical functioning have been identified. One suggestion has been a polymorphism in the gene encoding the Angiotensin Converting Enzyme, but the association was found only in small samples of young healthy males and elite athletes [Montgomery et al, 1998;Williams et al, 2000;Gayagay et al, 1998;Myerson et al, 1999], and not in all studies [Taylor et al, 1999;Rankinen et al, 2000a,b] and not among the elderly [Frederiksen et al, 2002]. A polymorphism in the gene encoding a receptor for vitamin D has been associated with grip strength in postmenopausal women, but only in a nonobese subgroup [Geusens et al, 1997].…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few specific genetic variants have been suggested to affect some of the phenotypes reflecting physical functioning. The findings from these and other studies have mostly been based on selected populations [i.e., young healthy males and elite athletes; Montgomery et al, 1998;Williams et al, 2000;Gayagay et al, 1998;Myerson et al, 1999] and have not been consistent [Taylor et al, 1999;Rankinen et al, 2000a,b;Frederiksen et al, 2002], or the association was confined to subgroups within the study sample [Geusens et al, 1997]. With respect to physical functioning, various different phenotypes [e.g., self-report; Christensen et al, 2000], a proportion of fast-twitch and slow-twitch fibers in skeletal muscle biopsies [Simoneau and Bouchard, 1995], magnetic resonance imaging of muscle mass [Gibbons et al, 1998], and measurement of maximal aerobic power (VO 2-max ) [Sundet et al, 1994] have been used in different studies, all of which suggested a genetic component to physical functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the association between the I allele of the ACE gene and superior performance capacity in elite endurance athletes [10,11,12], the relation between serum ACE activity and risk of severe hypoglycaemia could be explained by superior cognitive or overall performance of subjects with low ACE activity during hypoglycaemia. This is supported by the fact that measures of mild and biochemical hypoglycaemia were not affected by serum ACE activity, indicating that subjects, independent of their ACE activity, experience hypoglycaemia with equal frequency but that those with low ACE activity to a greater extent are able to compensate the condition by self-treatment or maintenance of near-normal function until the next pre-scheduled meal.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy humans both antecedent exercise and antecedent hypoglycaemia attenuate symptoms and hormonal counterregulation during subsequent hypoglycaemia [7,8]. In elite endurance athletes, who like patients with Type 1 diabetes spend considerable time with limited fuel availability, performance capacity has been associated with the angiotensin-converting enzyme (ACE) genotype as the insertion (I) allele of the ACE gene that confers low ACE activity, compared to the deletion (D) allele [9], has been linked to superior performance capacity [10,11,12].…”
Section: Following the Diabetes Control And Complicationsmentioning
confidence: 99%
“…The D allele has also been associated with increased risk of hypertension, diabetic renal complications and cardiovascular complications. Some studies have shown an association between ACE and physical performance [17][18][19], and it has been proposed that there may be a similarity in metabolic features between hypoglycaemia and exercise [8,20,21], such that patients with type 1 diabetes and the DD genotype are at increased risk of severe hypoglycaemia compared with those with the II genotype [21].…”
Section: Introductionmentioning
confidence: 99%